(untitled) (Annals of Medical Research, 2021)
Aim: The most common seizure type in childhood is febrile convulsion, which is likely to recur due to many risk factors. This study aimed to evaluate serum sodium and glucose levels in patients who had a febrile convulsion and investigate the relationship between these values and recurrent seizures.Materials and Methods: The medical records of patients presenting to our hospital with the diagnosis of febrile convulsion between 2013 and 2018 were investigated. Patients with high-risk factors for recurrence were excluded. According to the reference ranges of our laboratory, for glucose, 101-149 mg/dl as mild-to-moderate stress hyperglycemia, above 150 mg/dl as severe stress hyperglycemia; for sodium, below 134 mmol/L as hyponatremic.Results: Of the 90 patients, 51 were boys, and 39 were girls. Without recurrent convulsions with recurrent convulsions (first-last): The mean age was 27.2±12.7 months / 27.4 ± 11.3 months-30.5±12.4; the mean serum glucose level was 129.1±37 mg/dl/130 ±37.5 mg/dl-124 ± 34 mg/dl; the mean serum sodium level was 134.07±3.05 mmol/L 134.4 ± 2.6 mmol/L-133.8 ± 2.9mmol/L. The glucose level was 60-100 mg/dl in 14/5 cases, 101-149 mg/dl in 39/10 cases, and above 150 mg/dl in 16/6 cases; the sodium level was 135-150 mmol/L in 29/10 cases, 135 mmol/L in 40/11 cases.Conclusion: Febrile convulsion is in most cases present with hyponatremia and hyperglycemia, but this cannot be a predictive marker of seizure recurrence.